2014
DOI: 10.1371/journal.pone.0116386
|View full text |Cite
|
Sign up to set email alerts
|

N-Homocysteinylation Induces Different Structural and Functional Consequences on Acidic and Basic Proteins

Abstract: One of the proposed mechanisms of homocysteine toxicity in human is the modification of proteins by the metabolite of Hcy, homocysteine thilolactone (HTL). Incubation of proteins with HTL has earlier been shown to form covalent adducts with ε-amino group of lysine residues of protein (called N-homocysteinylation). It has been believed that protein N-homocysteinylation is the pathological hallmark of cardiovascular and neurodegenerative disorders as homocysteinylation induces structural and functional alteratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
26
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 58 publications
8
26
0
1
Order By: Relevance
“…The electropherograms showed a lower electrophoretic mobility for the modified proteins with an impaired biological function. In line with these results, many acidic proteins have been reported to form oligomers and aggregates upon modification by HTL [10,13,15,17], which may account for their lack of function. An explanation for the lower positive net charge observed in N-homocysteinylated proteins was given by Jakubowski [10], who reported that the e-amino group of lysine (pK = 10.5) is much more basic than the a-amino group of Hcy bound to lysine (eN(Hcy) lysine, pK = 7.1).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The electropherograms showed a lower electrophoretic mobility for the modified proteins with an impaired biological function. In line with these results, many acidic proteins have been reported to form oligomers and aggregates upon modification by HTL [10,13,15,17], which may account for their lack of function. An explanation for the lower positive net charge observed in N-homocysteinylated proteins was given by Jakubowski [10], who reported that the e-amino group of lysine (pK = 10.5) is much more basic than the a-amino group of Hcy bound to lysine (eN(Hcy) lysine, pK = 7.1).…”
Section: Discussionsupporting
confidence: 57%
“…Besides, it has been reported that Nhomocysteinylation may cause protein aggregation, as documented for several proteins [10,[13][14][15][16][17][18]. Several kinds of insults such as oxidative stress, ionizing radiation or drug exposure, as well as the pathophysiological accumulation of reactive metabolites in the body, can induce nonenzymatic post-translational modifications in proteins, thus causing the alteration of their functional properties and denaturation.…”
Section: Introductionmentioning
confidence: 99%
“…Our present data show that in insulin-producing cells HC toxicity requires higher concentrations than in other cell types, like endothelial cells [7] or neurons [48,52] as well as prolonged exposure. One of possible explanation for this difference could be the lack of a strong endogenous NO synthase expression in insulinproducing cells [53].…”
Section: Discussionmentioning
confidence: 54%
“…Other possible mechanisms might involve the inactivation of other components of the glycolytic flux or proteins, which affect the insulin secretory machinery by so-called N-homocysteinylation. The methionylated metabolite of HC, HC thiolactone, can modify proteins resulting in N-homocysteine-linked protein formation and can therefore influence protein structure and function, leading to enzyme inactivation, protein aggregation, and precipitation [38,48,49]. The modification by HC-thiolactone can be detrimental directly by affecting the function of an essential lysine residue or indirectly by interfering with the function of other essential residues or cofactors [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation